Commemorative plaque, St Thomas Cathedral - Ghosh, Ayan (2023)
St Thomas Cathedral has been a historic landmark within the Fort premise, from which Churchgate derives its name. The foundation stone of the church was laid in 1676, although the current building was consecrated for divine service on Christmas Day, 1718. It is the first Anglican church in Mumbai and at 300 years and counting, one of the oldest buildings in Mumbai.